Commentary on Afzali et al. (2019): Two data sets are better than one - Whelan, Robert (Society for the Study of Addiction, 2019)
The use of large data sets in addiction research iswelcome, because statistical power is increased. Whenapplied to large data sets, machine learning can help withinterpreting variable importance and with quantifyingreproducibility. However, application of machine learningin the real world requires consideration of several factors,such as economic cost.
Keywords: Addiction; Adolescence; Alcohol; Machine learning; Reproducibility; Team science